Costa Rican meat value chain description: price transmission as a tool - Rodríguez Lizano, Víctor (2016)
Price transmission analysis is an increasing research topic, especially for price taking countries such as Costa Rica. We describe the beef supply chain and provide a numerical implementation of Vector Error Correction Model (VECM) of price transmission for the meat market in order to observe the relationship between import prices of meat and their effects on national retail prices. To restore equilibrium, retail prices correct 8% of the error term monthly. Since the meat imports market of Costa Rica is complex, the analysis of others business partners as Nicaragua should be included in order to compare the influence of these in local retail prices.